Watchdogs, helpers or protectors? – Internal auditing in Malaysian local government - Ferry,, Laurence; Zakaria, Zamzulaila; Zakaria, Zarina; Slack, Richard E. (Elsevier Ltd, 2017)
This paper examines internal auditor roles to support public governance in a developing country context, through interviews with chief audit executives across 17 Malaysian Local Government Authorities. Drawing on critical theory, the research shows that internal auditors seek to legitimise their position through compliance (watchdog) and performance (helper and protector) audits. At the micro level of practices, in performing these dual roles, internal auditors are not colonised by governance rules and managerial influence, but instead are enabled by them to perform communicative action. Nevertheless, this was undermined by financial and managerial capacity issues that are a challenge in developing countries. © 2017 Elsevier Ltd